Análisis de la amenaza de inundación y elementos expuestos en el sector del malecón en la ciudad del Tena, en el periodo septiembre - diciembre 2024 - Vega Vaca, Víctor Jinson (2025)
Floods are recurring phenomena in the city, constituting a natural event that intensifies due to the increase in flow during the rainy period, which affects various locations. The objective of this research was to analyze the threat of flooding and the exposed elements in the scenic boardwalk sector of the city of Tena. To achieve this, a mixed methodology was used that integrates qualitative and quantitative approaches. The research focused on identifying the flood threat, for which historical data was collected from the Power NASA platform. In addition, various analytical methodologies were used, such as the Outlier technique for the identification of anomalies. Regarding return times, the Hydronomon software was applied, complemented by the Dick Peschke method. Based on these analyses, four hydraulic models were developed using IBER software, with the purpose of characterizing the elements exposed in the scenic boardwalk sector.